Trade openness and exchange rate management - Rodrigo Heresi; Eric Parrado (Inter-American Development Bank (IDB), 2023)
Singapore's unique monetary policy consists of a managed exchange rate framework that can be characterized as a Taylor-like reaction function with the nominal devaluation rate instead of the nominal interest rate as the main policy instrument. We build a small open economy New Keynesian model to estimate and characterize such a monetary rule from a welfare perspective. Welfare gains under an exchange rate rule (ERR) relative to the more standard interest rate-based Taylor rule (IRR) are unambiguously increasing in the degree of trade openness (defined as exports plus imports as a share of GDP). For Singapore, where trade openness is 280% of GDP, we estimate welfare gains of 1.48% of permanent consumption under an ERR. In a counterfactual thought experiment, we find that Chile, an established inflation-targeting economy using an IRR, would be better off under an ERR for any degree of openness above 100% (currently at 70%).
Keywords: E52; E58; F41; 330; Monetary policy; Exchange rate management; Open economy macroeconomics